Peran Self Efficacy Pada Servant Leadership Dalam Meningkatkan Kinerja Pada Badan Pendapatan Daerah Kabupaten Rokan Hilir - muslim, muslim; Adolf, Bastian Adolf; Afriana, Munthe Richa (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2025)
The purpose of this study is to conduct an in-depth analysis of the influence of servant leadership on employee performance at the Regional Revenue Agency (Bapenda) of Rokan Hilir Regency, with self-efficacy serving as a mediating variable. This research aims to provide a more comprehensive understanding of how a service-oriented leadership style can enhance employees’ confidence in performing their duties, which ultimately leads to improved performance. The population of this study includes all civil servants (ASN) working at Bapenda Rokan Hilir Regency, totaling 91 individuals. Due to the relatively small population size, the sampling method used is a saturated sampling technique, in which the entire population is included as the sample. Data collection was carried out using a systematically structured questionnaire distributed via Google Form. Data analysis was performed using the Structural Equation Modeling (SEM) approach with the assistance of SmartPLS 3.0 software. The results of the analysis indicate that both servant leadership and self-efficacy have a positive and significant influence on employee performance. Furthermore, servant leadership was also found to significantly enhance employees’ self-efficacy, which in turn mediates the influence of servant leadership on performance. These findings reinforce the importance of servant leadership in shaping employee self-confidence and driving optimal performance outcomes